OTORITAS ‘URF DALAM PENALARAN HUKUM ISLAM - Dr. Kholida Kholida (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
'Urf is one form of disputed reasoning. However, 'urf is always considered in all forms of reasoning, both qiyasi reasoning (istihsan bil 'urf) especially istislahi reasoning, because this reasoning is not based on specific texts (direct) but general arguments taking into account the benefits that will be obtained. The expressions of ushul experts show that 'urf reasoning has a big role in the formulation of law. Even for the current context, the application of 'urf as legal reasoning has a great opportunity for legal development. Because through 'urf reasoning it will be very easy for the Muslim community to practice the teachings of Islam itself. And making 'urf as reasoning in the formation of law is part of maintaining social stability that can lead to benefit as the ultimate goal of legal provisions.